RENDEMEN DAN KARAKTERISTIK EKSTRAK PEWARNA BUNGA KENIKIR (Tagetes erecta L.) PADA PERLAKUAN JENIS PELARUT DAN LAMA EKSTRAKSI - Puspadi Aristyanti, Ni Putu; Wartini, Ni Made; Wayan Gunam, I.B. (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2017)
Marigolds (Tagetes erecta L.) is an ornamental herb commonly used as a hedge plant with yellow petals especially in Bali, growing wild, and more flowering in direct sunlight exposed areas. Marigolds usually used for religion ceremonies and natural dye. The aims of this study were to determine the effect of solvent type and extraction time on the yield and characteristics of marigolds flower dye extract, and to determine the best solvent type and extraction time to produce marigolds flowers dye extract. The experiments in this study using factorial randomized block design with two factors. The first factor was the solvent type which consists of three levels: n-hexane, chloroform, and ethyl acetate. The second factor was extraction time that consists of three levels: 12, 24, and 36 hours. The results showed that the solvent type and time extraction time factor was affected significantly (P<0.01) on the yield, total carotenoids, the brightness level (L*), the redness level (a*) and the yellowish level (b*). Interaction between two factors was affected significantly (P<0.01) on the yield, total carotenoids and the redness level (a*). But, did not effect on the yellowish level (b*) and the brightness level (L*). The best treatment to produce marigolds flowers dye extract is use n-hexane solvent and extraction time 36 hours that result 9.68% (w/w) of yield, 20.21% (w/w) of total carotenoids, 8.25 of brightness level (L*), 4.04 of redness level (a*), and 2.86 of yellowish level (b*). Key words: marigolds flowers dye extract, solvent type, extraction time